2017
DOI: 10.4081/tmr.6598
|View full text |Cite
|
Sign up to set email alerts
|

The role of mouse models in translational cancer research: present and future directions

Abstract: A major issue in the research for new anticancer therapeutics is represented by the low number of new compounds approved for clinical use in comparison to the good success rate reported in preclinical studies. This high attrition rate could be attributed to many factors including the unsatisfactory predictive value of experiments performed in animals. To this purpose, general opinions suggest that classical models as murine tumors and xenografts do not mimic the complexity of human cancer diseases and that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Specific mutations in Kras and P53 in lung cancer GEMMs have shed light on the NFκB pathway's role in tumor development, offering potential therapeutic targets. In HCC, GEMMs have highlighted the importance of genetic diversity in understanding tumor subtypes, providing a platform for bench-to-bedside research, especially with systems allowing for the controlled overexpression of genes like MYC, relevant to human carcinomas (69,70).…”
Section: Genetically Engineered Mouse Models (Gemms) For Cancer Researchmentioning
confidence: 99%
“…Specific mutations in Kras and P53 in lung cancer GEMMs have shed light on the NFκB pathway's role in tumor development, offering potential therapeutic targets. In HCC, GEMMs have highlighted the importance of genetic diversity in understanding tumor subtypes, providing a platform for bench-to-bedside research, especially with systems allowing for the controlled overexpression of genes like MYC, relevant to human carcinomas (69,70).…”
Section: Genetically Engineered Mouse Models (Gemms) For Cancer Researchmentioning
confidence: 99%
“…From translational aspects, the discovery demonstrated that the use of antagonists to this pathway can help destroy cancerous cells. By using GEMMs, effective therapeutic preparations for various subtypes of different cancers and cancers with the same histological features can be developed 52 . Hepatocellular carcinoma (HCC) has three subtypes each of which has almost similar survival but due to heterogeneous tumor properties but genetically engineered mice could be effective in the bench‐to‐beside research applications because of the possible genetic modifications.…”
Section: Genetically Engineered Mouse Modelsmentioning
confidence: 99%